Gecko (Gekko gecko) Captive Breeding Development Strategy In East Java - Bugiono, Bugiono; Raharjo, Dadik; Hidanah, Sri; Soeharsono, Soeharsono; Ardianto, Ardianto; Setyawan, Boedi (El-Hayah:Jurnal Biologi, 2024)
Geckos (Gekko gecko) are widely used in traditional Chinese medicine and are reported to have anti-tumor properties. Approximately 93% of reptiles exported from Indonesia come from the wild. The direct and continuous capture of geckos in nature will threaten gecko populations in the future. As an effort to control the possible threat of extinction, the Indonesian government encourages the utilization of this animal through captive breeding activities. The existence of gecko (Gekko gecko) captive breeding units in East Java has not been widely developed and still uses conventional and semi-natural patterns. Periodic evaluations need to be carried out to determine whether or not this breeding activity is feasible and what the development strategy is in the future. This study aims to analyze the strengths, weaknesses, opportunities and threats in order to formulate a business development strategy for gecko breeding in East Java. This research uses a survey method by analyzing and describing the problems in the field, while the technical analysis uses internal factor analysis (IFE matrix), external factor analysis (IFE matrix) and SWOT analysis. Based on the results of the SWOT analysis, the development strategy of the gecko (Gekko gecko) breeding business in East Java includes: maintaining market confidence and maintaining quality and production stability; adjusting government regulations related to gecko trade governance; developing effective breeding methods; adjusting government regulations related to breeding governance; establishing market strategies and production stability to suppress illegal trade; and researching new market potential for gecko trade development